The principle of effective legal protection in administrative law : a European perspective - Szente, Zoltán; Lachmayer, Konrad (Routledge, 2016)
This collection presents a comparative analysis of the principle of effective legal protection in administrative law in Europe. It examines how European states consider and enforce the related requirements in their domestic administrative law. The book is divided into three parts: the first comprises a theoretical introductory chapter along with perspectives from International and European Law; part two presents 15 individual country reports on the principle of effective legal protection in mostly EU member states. The core function of the reports is to provide an analysis of the domestic instruments and procedures. Adopting a contextual approach, they consider the historical, political and legal circumstances as well as analysing the relevant case law of the domestic courts; the third part provides a comparative analysis of the country reports. The final chapter assesses the influence and relevance of EU law and the ECHR. The book thus identifies the most important trends and makes a valuable contribution to the debate around convergence and divergence in European national administrative systems.
Keywords: Abuse of administrative power -- Europe.; LAW -- Constitutional.; LAW -- Public.; Abuse of administrative power.; Europe.; Biographies.; Electronic books.